Algoritma Linear Regression dalam Memprediksi Pertumbuhan Jumlah Penduduk Menurut Provinsi dan Jenis Kelamin - Bella Aprianti; Anisa Aulia; Intan Purnamasari (Jurnal Ilmiah Wahana Pendidikan, 2022)
Basically the population in a country will continue to increase every year. According to the Central Statistics Agency (BPS), Indonesia's population in 2015 continued to increase until 2020. The increasing population growth will have an impact on the economic, social, political and national defense sectors. Proper structured planning by the government is needed to avoid the possible impacts. Researchers predict population growth using the Linear Regression Algorithm in prediction techniques in data mining. The results of the Linear Regression Algorithm are almost perfect because they are very close to the original data, and the resulting accuracy is very good. The lowest RMSE result is 125,321.